2021
DOI: 10.3389/fchem.2021.650587
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-Based Nanomaterials for Cancer Therapy

Abstract: Nanotechnology advances in cancer therapy applications have led to the development of nanomaterials that generate cytotoxic reactive oxygen species (ROS) specifically in tumor cells. ROS act as a double-edged sword, as they can promote tumorigenesis and proliferation but also trigger cell death by enhancing intracellular oxidative stress. Various nanomaterials function by increasing ROS production in tumor cells and thereby disturbing their redox balance, leading to lipid peroxidation, and oxidative damage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 113 publications
0
35
0
Order By: Relevance
“…In the mechanism of determining the cytotoxicity of β-Cu 2 O NPs, oxidative stress plays an important role because when the cells are exposed to β-Cu 2 O NPs, the level of 8-isoprostane and the ratio between oxidized and total glutathione in the cells increased significantly with a high level of oxidative stress in cells. In vitro studies using cultured A-549 lung carcinoma cell lines have shown that exposure to β-Cu 2 O NPs led to an increase in intracellular reactive oxygen species (ROS) formation and cell death . Rushton et al showed that the native oxidant potential of β-Cu 2 O NPs as determined via oxidation of dichlorodihydrofluorescein (DCFH) and others correlates with the production of oxidant stress-related inflammatory mediators in cultured carcinoma cell lines .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mechanism of determining the cytotoxicity of β-Cu 2 O NPs, oxidative stress plays an important role because when the cells are exposed to β-Cu 2 O NPs, the level of 8-isoprostane and the ratio between oxidized and total glutathione in the cells increased significantly with a high level of oxidative stress in cells. In vitro studies using cultured A-549 lung carcinoma cell lines have shown that exposure to β-Cu 2 O NPs led to an increase in intracellular reactive oxygen species (ROS) formation and cell death . Rushton et al showed that the native oxidant potential of β-Cu 2 O NPs as determined via oxidation of dichlorodihydrofluorescein (DCFH) and others correlates with the production of oxidant stress-related inflammatory mediators in cultured carcinoma cell lines .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies using cultured A-549 lung carcinoma cell lines have shown that exposure to β-Cu 2 O NPs led to an increase in intracellular reactive oxygen species (ROS) formation and cell death. 18 fluorescein (DCFH) 19 and others correlates with the production of oxidant stress-related inflammatory mediators in cultured carcinoma cell lines. 15 Surface-enhanced modified biocatalytic precursor-based carcinoma therapeutics increases exponentially every year.…”
Section: Introductionmentioning
confidence: 99%
“…Since the therapeutic performance of nanoceria is related directly to its ability to raise the ROS to cytotoxic levels in tumor cells, , the ROS generation levels in A375-P and A375-MA1 cells treated with nanoparticles at 48 h were measured. Figure B shows these ROS levels, as detected by the DCFDA assay and MitoSox assay.…”
Section: Resultsmentioning
confidence: 99%
“… 43 In addition, oxygen radicals and superoxide anions can also increase the instability of cell membranes through lipid peroxidation chain reactions, disrupt cellular mitochondrial function, and trigger DNA unzipping inducing cellular necrosis or autophagy and ultimately leading to tumor cell death. 44 …”
Section: The Mechanism Of Sdtmentioning
confidence: 99%